Peran GDP dalam Memoderasi Pengaruh Environmental, Social, Governance (ESG) terhadap Kinerja Perusahaan dalam Sektor Jasa di Negara Asean-5 Periode 2019–2023 - Rafinka, Syadinda Azra; Sidjabat, Mona Ridho (Jurnal Manajemen dan Usahawan Indonesia, 2025)
This study analyze the role of GDP in moderating the influence of environmental, social, governance (ESG) on the performance of service sector companies. The data is collected from Refinitiv Eikon Database including 81 sample companies in the services sector in ASEAN-5 countries for the period 2019–2023 that have complete ESG combined score and individual pillar scores (environmental, social and governance) of each company. This study uses balanced panel data with fixed effect robust model estimation. The results show that environmental score and ESG combined score have a significant negative effect on firm performance. However, there is no significant effect of social score and governance score on firm performance. Furthermore, GDP is negatively significant in moderating the effect of environmental score, social score, and ESG combined score on firm performance. However, GDP is not significant in moderating the effect of governance score on firm performance